Effect of ordering of B’ site atom on the dynamical lattice properties of sustainable Sr2B′WO6 (B’= Co, Ni) double Perovskite - Neetu Malik; Ruby Jindal; Archana Tripathi; Neeraj Kumari (Chemical Physics Impact)
The wavenumbers of Raman and infrared spectra for environment friendly double perovskite Sr2B′WO6 (B’= Co, Ni) of I4/m phase (No.-87) has been analyzed using Wilson's GF matrix method. Theoretical assignments for the Raman and infrared wavenumbers for Sr2CoWO6 and Sr2NiWO6 compounds have been reported for the very first time. As far as we know, no theoretical assignments have been made for the infrared frequencies of Sr2CoWO6 and Sr2NiWO6 compounds in the I4/m phase. Both compounds are Lead-free oxide double perovskites which are emerging as a sustainable alternative to lead-based versions, offering similar electronic, optical, and magnetic properties without the associated environmental and health risks. A robust correlation with the B’ site has been identified across a range of frequencies, providing insights into the structural details of the examined compounds. The force constants related to the B’-site atom exhibit a consistent trend and reveal variations in values with changes in atomic orbitals. Moreover, frequencies influenced primarily by the B’ atoms display distinct characteristics with the variation of atomic number, emphasizing the considerable effect of the B’ atom's size on vibrational properties. The frequencies determined in this research align well with experimentally observed frequencies. Additionally, an exploration of potential energy distributions (PED) delves into the influence of interatomic forces on the computed Raman and infrared phonon modes for these materials.